2009
DOI: 10.1007/s11090-009-9174-2
|View full text |Cite
|
Sign up to set email alerts
|

Remote Oxygen and Nitrogen Plasma Inactivation of Staphylococcus aureus: Effects and Mechanisms

Abstract: The distribution of active species in remote oxygen and nitrogen plasma and the germicidal effect (GE) of Staphylococcus aureus on the surface of medical poly(tetrafluoroethylene), polyvinyl chloride and polyethylene terephthalate films, which had been widely used in medical devices, were studied. The results showed that the concentration of electrons and ions decreased rapidly with increasing the distance from the center of induction coil, which approximated to 0 at 40 cm, whereas the concentration of both ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The mode of action of plasma species is more complex in microbial inactivation. Fast etching actions of electrons, ions and radicals on cell membranes are known to induce bacteria death, and have been the primary reasons for oxygen and nitrogen plasma inactivation . The inelastic collisions are responsible for the effective energy transfer from reactive species to other molecules in plasma .…”
Section: Resultssupporting
confidence: 89%
“…The mode of action of plasma species is more complex in microbial inactivation. Fast etching actions of electrons, ions and radicals on cell membranes are known to induce bacteria death, and have been the primary reasons for oxygen and nitrogen plasma inactivation . The inelastic collisions are responsible for the effective energy transfer from reactive species to other molecules in plasma .…”
Section: Resultssupporting
confidence: 89%
“…Nitrogen and oxygen are the major constituents of air. It has been reported that fast etching action on cell membrane by electrons, ions and radicals are primary reasons of oxygen and nitrogen plasma inactivation, which leads to the cellular contents effuse and engender bacteria death (Zhang & Chen, 2009). Also, an electrostatic mechanism may potentially contribute to biological effects of corona discharges (Timoshkin et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%